Acute effects of exercise mode and volume on blood pressure in stroke patients - Reis, Pedro; Lochmann, Matthias (2011)

Comparison of the AMICA and the InfoMax Algorithm for the Reduction of Electromyogenic Artifacts in EEG Data - Leutheuser, Heike; Gabsteiger, Florian; Hebenstreit, Felix; Reis, Pedro; Lochmann, Matthias; Eskofier, Björn (IEEE EMBC 2013, 2013)

ICA-based Reduction of Electromyogenic Artifacts in EEG Data: Comparison With and Without EMG Data - Gabsteiger, Florian; Leutheuser, Heike; Reis, Pedro; Lochmann, Matthias; Eskofier, Björn (IEEE EMBC 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.icabas

Localization of Scopolamine Induced Electrocortical Brain Activity Changes, in Healthy Humans at Rest - Reis, Pedro; Eckhardt, Holger; Denise, P; Bodem, F; Lochmann, Matthias (Journal of Clinical Pharmacology, 2013)
To prevent the participants of parabolic flights from nausea they are optionally treated with subcutaneously injected antiemetic scopolamine. The range of side effects of this substance include reductions of the a-2 frequency band. Previous studies, however, have given no information as to which generator centers are responsible for this effect. The objective of this study therefore, is to identify the cortex area that may be responsible for this effect. Six participants were subcutaneously administered 0.7 mg of scopolamine. EEG was recorded for 10 minutes before to 20 minutes after injection. Data preprocessing followed including filtering and artifact minimization. A statistical analysis was performed with sLORETA/eLORETA software for each subject over a time window from 3 minutes before to 17-20 minutes after scopolamine injection. Results show, that in the BA7, the precuneus, on both hemispheres suffered a a-2 activity decrease in absolute power. The identified brain cortex center is an important hub with high connectivity and centrality values within the neural network. It contributes to the control of movement and to space orientation. Therefore, an activity alteration in this area can possibly explain the antiemetic effect of scopolamine and open a window to understand the origin of motion sickness. © The Author(s) 2013.
UnivIS-Import:2015-03-09:Pub.2013.phil.dps.iss.pspbio.locali
Keywords: Brain mapping; Electroencephalography; Motion sickness; Parietal lobe; Scopolamine hydrobromide

Methodological aspects of EEG and body dynamics measurements during motion - Reis, Pedro; Hebenstreit, Felix; Gabsteiger, Florian; von Tscharner, Vinzenz; Lochmann, Matthias (Frontiers in Human Neuroscience, 2014)
EEG involves the recording, analysis, and interpretation of voltages recorded on the human scalp which originate from brain gray matter. EEG is one of the most popular methods of studying and understanding the processes that underlie behavior. This is so, because EEG is relatively cheap, easy to wear, light weight and has high temporal resolution. In terms of behavior, this encompasses actions, such as movements that are performed in response to the environment. However, there are methodological difficulties which can occur when recording EEG during movement such as movement artifacts. Thus, most studies about the human brain have examined activations during static conditions. This article attempts to compile and describe relevant methodological solutions that emerged in order to measure body and brain dynamics during motion. These descriptions cover suggestions on how to avoid and reduce motion artifacts, hardware, software and techniques for synchronously recording EEG, EMG, kinematics, kinetics, and eye movements during motion. Additionally, we present various recording systems, EEG electrodes, caps and methods for determinating real/custom electrode positions. In the end we will conclude that it is possible to record and analyze synchronized brain and body dynamics related to movement or exercise tasks. © 2014 Reis, Hebenstreit, Gabsteiger, von Tscharner and Lochmann.
UnivIS-Import:2015-04-14:Pub.2014.phil.dps.iss.pspbio.method
Keywords: Artifacts reduction; Electrodes digitalization; Electroencephalography; Hardware and software; Methodology; Movement and exercise

Neuronal correlates of product feature attractiveness - Schön, Franziska; Reis, Pedro; Rampp, S; Lochmann, Matthias (2015)

Scopolamininduzierte Alpha-2-Desynchronisation der elektrokortikalen Aktivität (EEG) des Lobus parietalis superior - Lochmann, Matthias; Eckhardt, Holger; Reis, Pedro; Hoffmann, H-U (2011)

SVM for Semi-automatic Selection of ICA Components of Electromyogenic Artifacts in EEG Data - Gabsteiger, Florian; Leutheuser, Heike; Reis, Pedro; Lochmann, Matthias; Eskofier, Björn (The 15th International Conference on Biomedical Engineering, 2013)

Using a motion capture system for spatial localization of EEG electrodes - Reis, Pedro; Lochmann, Matthias (Frontiers in Human Neuroscience, 2015)
Keywords: motion; capture; System; spatial; Localisation; EEG